N-3 PUFA-ENRICHED HEMP SEED DIET MODIFIES BENEFICIALLY SOW MILK COMPOSITION AND PIGLETS’ PERFORMANCES - Mihaela HĂBEANU; Anca GHEORGHE; Ioan SURDU; Veronica Sanda CHEDEA; Nicoleta Aurelia LEFTER; Gheorghe STOIAN; Andreea-Anne–Mary-Dolores PANAIT; Ionuț B (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
An experiment was conducted to evaluate the dietary hemp seed (HS) influence on sow milk composition and piglets’ performances. Ten sows were assigned randomly, to a control group (CL) with classical diets, and an experimental group (HSL) fed with 5% HS. Their litter (N=96) were divided in two groups: HH/CH with 1.5% HS and CC/HC without HS. The HS antioxidant activity was determined by DPPH method, phenolic compound by Folin–Ciocalteu, cannabinoid by colorimetry. Milk and colostrum samples from sow were collected manually. Gas chromatography was used to determine milk fatty acids (FA) composition. Colostrum and sow milk content of protein was determined by biuret reaction and lactose concentration was determined using phosphomolybdenic reagent. The lipid specimen was heated with concentrated sulfuric acid. Then vanillin and phosphoric acid are added to yield a pink coloured product which has been measured at 530 nm and quantified using a triolein standard. Milk yield (MY) was calculated. Average daily gain (ADG) of piglets at 0 to 7 d (days) was higher (P= 0.001) for HC/HH group and tended to be higher for HC/ HH group at 0-21 d. Milk yield calculated at peak lactation was > 2.1-fold in HSL group than in CL group. The diets tend to influence milk fat content, whereas the day had a significantly higher influence for protein and lactose. The n-3-rich diet favours milk deposition of α-linolenic FA (ALA), linoleic FA (LA) and total n-3 polyunsaturated FA (PUFA). This led to a significantly lower n-6:n-3 ratio in milk of HSL group. Docosahexaenoic FA (DHA) increased 1.87 and 2.33-fold at 0-7 d and 0-21 d in HSL group. We can conclude that HS altered beneficially milk FA associated with litter performance. Significantly positively correlated with MY, milk constituents declined in time.